General patterns and drivers of changes in employment structure: Evidence from five European countries - Yakymova, Larysa (Alexandru Ioan Cuza - University of Iasi, 2020)
This paper seeks to answer whether the general patterns and drivers of the sectoral employment shifts depend on a country’s level of development. To accomplish this, we examined employment in Germany, Hungary, Poland, Romania and Ukraine at the national level (1998-2018) using econometric analysis, and at the regional NUTS2 level (2009-2018) using shift-share analysis. We obtained evidence that the general trend is the service sector expansion. Using the ARDL approach and the Granger causality test, we identified long-run unidirectional causality running from income proxies to employment in services in all countries except Romania, where the opposite causality was found. We revealed that household income moderates the impact of urbanization on service sector growth in all countries except Poland. At the regional level, the change in the employment rate in services is explained by the national growth effect and slightly by the industry-mix effect if the active phase of structural changes is completed.
Keywords: sectoral employment; ARDL bounds test; Granger causality; moderation effect; shift-share analysis.